Isu Terorisme Dalam Bingkai Majalah Isra’ (Analisis Framing Berita Terorisme Pada Majalah Isra’ Rubrik ‘Suara Khadijah’) - Dendy H Nanda (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2022)
This study wants to answer how Isra Magazine 'frames the issue of terrorism' in the 'Voice of Khadijah' rubric. This study uses a qualitative approach by analyzing news texts on the issue of terrorism using framing device Robert N. Enmant as an analytical tool, namely Define Problem, Causal Interpretation, Moral Evaluation, and Treatment Recommendation. The results of this study found three main frames in the coverage of Isra' Magazine related to the issue of terrorism, namely, first, violations of legal procedures. Police officers (especially Detachment 88) violated legal procedures in an effort to deal with suspected terrorist acts, both in terms of raids, arrests, detentions, and trials. Second, violations of human rights (HAM). The alleged perpetrators of terrorism and their families have become victims of human rights violations by the police and mainstream media reports. Third, the mainstream media is not neutral and objective in covering terrorism. The coverage carried out by the mainstream media often discredits suspected terrorist acts and their families. The mainstream media is accused of being just a mouthpiece for the government, in this case the police. Thus, it can be concluded that Isra' Magazine's position in looking at terrorism issues is that there is a tendency for Isra' Magazine to “defend” suspected terrorist acts and place state apparatus and mainstream media as sources of problems, even though from the beginning they emphasized that there was no special agenda to defend terrorism.